TERMINOLOGICAL ANALYSIS OF THE POPULATION MIGRATION PROCESS - Saipova Malaxat (TADQIQOTLAR, 2025)
Annotation. The article examines the development of population migration and lists  the  stages  of  this  process  as  proposed  by  scholars.  Additionally,  it  analyzes definitions of the term "migration" provided by both domestic and foreign researchers and presents the author's own definition.